Profil Mortalitas Stroke Associated Pneumonia Tahun 2016-2017 - Anna Mardiana Ritonga; Syahrizal Syarif; Lyna Soertidewi (Poltekkes Kemenkes Jakarta III, 2019)
Stroke associated pneumonia (SAP) is the most common complication after stroke and has a high mortality rate. SAP mortality profile among Neuro ICU patients has not been fully investigated. Knowledge of mortality profiles can help clinical decision making for patient management. The purpose of this study was to determine the mortality profile of SAP who were treated in the Neuro ICU National Brain Centre (NBC) Hospital. This was a retrospective cohort study of the patients were hospitalized in the Neuro ICU NBC Hospital, who were diagnosed with SAP during 2016-2017. Clinical and laboratory data and the patient's status during treatment are obtained from medical record data. A total of 197 stroke patients who were treated at the Neuro ICU NBC Hospital during 2016-2017, there were 130 (65.98%) patients diagnosed with SAP, with mortality during treatment of 77.7%. The highest SAP mortality was found in male patients (75%), in the age group ≥ 60 years (55.4%), GCS at admission ≤ 8 (88.3%), accompanied by hypertension (66.7%) and leukocytosis (74.8%). In bivariate analysis, the variables that were statistically significant (p <0.05) were hypertension, GCS, LoS, APACHE II score, and PMR.